Effect of exposure of teeth to Ph change of chlorinated water on shear bond strength of metal orthodontic brackets (an in vitro study) - Eman A. Mustafa; Seham A. Hanafy; Tarek N. Yousry; Hanan A. Ismail (BMC Oral Health)
Abstract Background Swimming is widely recognized as one of the healthiest forms of exercise, but chlorinated water in swimming pools can adversely affect orthodontic bracket bonding. The objective of this study was to determine the effects of chlorinated water with varying pH levels on the shear bond strength (SBS) of metal brackets and to assess the adhesive remnant index (ARI) following bracket debonding. Materials and methods A total of 126 sound premolars (71 maxillary and 55 mandibular) were randomly divided into three experimental groups: two test groups and one control group. In the test groups (Groups 1 and 2), the teeth were soaked in chlorinated water at two different pH values (pH 7.4 and pH 3), whereas in the control group (Group 3), the teeth were soaked in artificial saliva (pH 7). The soaking period lasted for 12 days to simulate one year of swimming training. A consistent bonding protocol was applied for all the samples. Each group was further randomly divided into three subgroups of 14 premolars to compare the SBS and ARI values immediately after bonding (Subgroup 1), after 6 days of bonding (mimicking 6 months of training) (Subgroup 2), and after 12 days of bonding (mimicking one year of training) (Subgroup 3). Results In all the subgroups, the control group consistently had a higher SBS than did the test groups. Compared with Group 1, Group 2 had a significantly lower SBS. Specifically, the means and standard deviations in Group 1 were 7.34 ± 0.99 MPa for Subgroup 1, 6.89 ± 0.95 MPa for Subgroup 2, and 5.59 ± 1.09 MPa for Subgroup 3. In Group 2, the values were 6.12 ± 0.72 MPa for Subgroup 1, 5.82 ± 0.70 MPa for Subgroup 2, and 4.52 ± 0.86 MPa for Subgroup 3. Conversely, Group 3 presented means and standard deviations of 9.01 ± 0.99 MPa for Subgroup 1, 9.06 ± 0.91 MPa for Subgroup 2, and 9.10 ± 0.92 MPa for Subgroup 3. The ARI values were not significantly different between the groups. Conclusion The pH of chlorinated swimming pool water affects the bond strength of orthodontic brackets, with a more acidic pH resulting in diminished bond strength. Accordingly, continuous monitoring of the pH of swimming pool water is essential.